Imagining the next ten years of megadisasters : exploring the future of UNICEF’s humanitarian work through the lens of children - Quinelato, Thais Croco (2024)
This study explores high-impact, low-probability scenarios traditionally overlooked by UNICEF/RAPS. By examining the cumulative effects of megadisasters on children's well-being, this research provides new insights into these critical scenarios. Utilizing desk research, expert interviews, and quantitative data analysis, the study culminates in an interactive simulation featuring character-based vignettes. These vignettes depict the realities children face during complex megadisasters and forecast the impacts on their lives, offering a robust tool for understanding and preparing for these events.